WHICH WAY IS NIGERIA HEADING? THE POST-COLONIAL POLITICAL SYSTEM AND DEVELOPMENTAL ISSUES - Bamidele, Seun (PEOPLE: International Journal of Social Sciences, 2018)
This article explores development challenges in Nigeria through a qualitative methodological approach. In explaining the challenges pitting Nigerian economy and development, the objectives adopt modernization and dependency theories for analysis. The information gathered from the field suggests that there is the need for the blend of the Nigerian pre-colonial traditional systems with the post-colonial political system in addressing developmental issues. An overhaul of the existing political systems to accommodate Nigerian traditional and democratic punitive measures in addressing the country developmental challenges is prescribed. The ingenuity in pre-colonial traditional system cannot be overemphasized hence, the paper concludes that, for Nigeria to achieve the status quo of developed nations, a lot of works and review needs to be done internally in the Nigerian political systems and institutional structures to eschew the external forces and pressures causing backwardness in our political and economy development in Nigeria.